Zero-Divisor Graphs, Commutative Rings of Quotients, and Boolean Algebras - LaGrange, John D. (Trace: Tennessee Research and Creative Exchange, 2008)
The zero-divisor graph of a commutative ring is the graph whose vertices are the nonzero zero-divisors of the ring such that distinct vertices are adjacent if and only if their product is zero. We use this construction to study the interplay between ring-theoretic and graph-theoretic properties. Of particular interest are Boolean rings and commutative rings of quotients.